GCSE chemistry - McDuell, Bob (Letts, London, 1994)
Chemistry text which is one of a series covering the GCSE/Key Stage 4 Programmes of Study and Attainment Targets set out by all the major examining bodies. Features include guidance on studying, revising, coursework and types of assessment questions; exercises and projects; and exam questions.